Use of the Composite Pedicled Pectoralis Minor Flap after Resection of Soft Tissue Sarcoma in Reconstruction of the Glenohumeral Joint - Michiel A. J. van de Sande; Tom Cosker; Stephen M. McDonnell; C. L. M. H. Gibbons; Henk Giele (Case Reports in Orthopedics)
The surgical repair of an extensive anterior glenohumeral soft tissue defect is complicated by glenohumeral instability and subsequent significant functional deficit. This surgical note offers a relatively simple reconstruction of the anterior capsule and subscapularis muscle using a pectoralis minor pedicle flap. This reconstruction is supplemented with functional reconstruction of the anterior glenohumeral joint. A conventional deltopectoral approach is utilized and pectoralis minor is freed from its coracoid insertion, released, and mobilized without compromising the pedicle entering from the dorsum and inferior one-third of the muscle. The mobilized pectoralis minor vascular pedicle has sufficient length for the pectoralis minor to be transferred to provide coverage of the anterior shoulder joint even in full external rotation, providing anterior stability. To further improve glenohumeral stability and shoulder function, the pectoralis major muscle can be split with the clavicular part reinserted lateral to the bicipital groove onto the lesser tuberosity replacing subscapularis function while stabilising the glenohumeral joint.